The aesthetics of linear formations in the Kiswah of the Holy Kaaba: installation systems as a model - Berghout, Abdul Aziz; Mohammaed Alashari, Duaa (Alanya University, 2024)
The Kiswah of the Holy Kaaba possesses aesthetic values and dimensions embodied through the artistic composition of Arabic calligraphy, and this artistic composition is considered a wonderful aesthetic artistic issue that arouses admiration, appreciation and reverence. Therefore, this study aims to reveal the aesthetic systems with plastic artistic values present in the linear formations embodied in the dress of the Holy Kaaba, according to a methodological perspective and an artistic vision. The question that arises, which embodies the research problem, is gathered by the researcher into a main question: Can the researcher analyze the aesthetic systems of Arabic calligraphy and calligraphic formations in the covering of the Holy Kaaba and formulate them in a contemporary artistic language? Based on the nature of the study and the goals it seeks to achieve, the researcher used the content analysis approach, which is an approach suitable for this type of aesthetic study related to describing works of art. Regarding the study tool, observation will be the fundamental tool used in this study. The study population is represented by the collection of Arabic calligraphy and calligraphic formations in terms of the semantic and aesthetic functions of the covering of the Holy Kaaba. The study reached several results: the covering of the Kaaba, with its Arabic calligraphy and calligraphic formations, expresses the authenticity of the Islamic nation and the aesthetic dimension inherent within the scope of Islamic art. Arabic calligraphy is characterized by aesthetic characteristics that make it a decorative element, as it contains many artistic and aesthetic values, and specifically the clear, complex Thuluth calligraphy. This helped him form Arabic calligraphy with different plastic artistic systems and a high aesthetic that adorned the covering of the Holy Kaaba. The study also found that the totality of calligraphic compositions was formulated in an eloquent aesthetic, artistic style that added to the beauty of the verbal meaning with the beauty of the calligraphic composition. In this, the visual eloquence and the beauty of the textual structure were demonstrated, based on the ability of Arabic le